Exploring the potential of assessment efficacy in sports coaching - A Commentary - Cassidy, T. (International Journal of Sports Science and Coaching, 2012)
One possible reason for why elite competition coaches may not readily engage with eCaps is because its design appears to favour a context that is more akin to formal education where the explicit function is education and learning. This is illustrated in the description of the first element of eCaps which stated that an instructor would produce and provide "practical demonstrations of coaching techniques by experts in the particular sporting field…[which] would be tailored to communicate and exemplify the authentic response characteristics expected of the developing coach". The author is convinced that this would be valued because it is well documented that formal coach education has little effect on the coaching practice of elite coaches.